Diatomaceous rocks of the Jawornik deposit (the Polish Outer Carpathians): petrophysical and petrographical evaluation. - Figarska-Warchoł, Beata; Stańczak, Grażyna; Rembiś, Marek; Toboła, Tomasz (Geology, Geophysics and Environment, 2016)
AbstractDiatomites are identified as a group of the critical minerals that are essential to many industrial applications due to a unique combination of their physical properties, i.e. porous and permeable structure, high specific surface area and adsorption capacity, low density and thermal conductivity, and chemical inertness. The present study was undertaken to analyse the relationships between the pore network characteristics, petrophysical parameters, and mineralogical variability of the Lower Miocene diatomites from the Jawornik deposit (Skole Unit, the Polish Outer Carpathians, SE Poland). Five varieties of the diatomites, distinguished on the basis of the macroscopic features, i.e., colour and fracturing effects, have been investigated by SEM, chemical and XRD analysis, mercury intrusion porosimetry, helium pycnometry, and the Vickers hardness tests. Significantly differing are two varieties. The light-coloured, massive and block-forming diatomites consist mainly of poorly cemented siliceous skeletal remains of diatoms, and represent the rocks with high porosity, low bulk density and low microhardness. The dark-gray silicified diatomites with a platy or prismatic splitting reveal obscured microfossils of diatoms and are the most compact and hard rocks, with poor porosity and higher bulk density. The spatial distribution of the field identifiable rock varieties allows selective exploitation of the diatomites with the predictable petrophysical characteristics that define their future use.